2016
DOI: 10.1177/0894439316639561
|View full text |Cite
|
Sign up to set email alerts
|

One Step, Two Step, Network Step? Complementary Perspectives on Communication Flows in Twittered Citizen Protests

Abstract: The article analyzes the nature of communication flows during social conflicts via the digital platform Twitter. We gathered over 150,000 Tweets from citizen protests for nine environmental social movements in Chile, and use a mixed-methods approach to show that longstanding paradigms for social mobilization and participation are neither replicated nor replaced, but reshaped. In digital platforms, long standing communication theories, like the 1955 two-step flow model, are still valid, while direct one-step fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 39 publications
2
55
0
4
Order By: Relevance
“…Likewise, Hilbert, Vásquez, Halpern, Valenzuela, & Arriagada (2017) analyzed the nature of communication flows during social conflicts on Twitter in the context of Chile, concluding that long-standing paradigms for social mobilization and participation are neither replicated nor replaced but reshaped.…”
Section: The Two-step Flow Of Communicationmentioning
confidence: 99%
“…Likewise, Hilbert, Vásquez, Halpern, Valenzuela, & Arriagada (2017) analyzed the nature of communication flows during social conflicts on Twitter in the context of Chile, concluding that long-standing paradigms for social mobilization and participation are neither replicated nor replaced but reshaped.…”
Section: The Two-step Flow Of Communicationmentioning
confidence: 99%
“…Thus, the Chilean context is similar to other Western countries experiencing high SNS use and protest activity, but increased voter apathy. Additionally, prior studies of Chile have found that social media use has played a role in triggering citizen-led direct political action (Hilbert et al, 2017).…”
Section: Study Contextmentioning
confidence: 99%
“…In other words, they create, receive, and disseminate supportive messages through central network positions. This network approach provides (1) a complementary perspective to previous studies that employed content analysis techniques to describe messages on OHCs, and (2) a visualization of relational connections in online weak-tie networks that may not be present in offline networks (Hilbert et al, 2016). Furthermore, by integrating the diffusion of innovation theory and the social support literature, this study also addresses the calls to apply multilevel and network perspectives to support mobilization within online support communities (Wright, 2016).…”
Section: Theoretical Implicationsmentioning
confidence: 99%